Social Technology Canvas: methodology for creating projects (Research, Society and Development, 2022)
Brazil has several social problems and Social Technology (TS) is an alternative for the construction and implementation of solutions that aim to reduce inequalities and improve the quality of life of communities. However, it lacks adequate methodologies that can guide its creation process. Thus, this article presents a project modeling tool for use in the creation of TS, developed based on the Business Model Canvas. For this, a descriptive research was developed, with a qualitative approach through narrative bibliographic analysis. As a result of the study, the Canvas of Social Technology is presented, whose differential is the attendance to the aspects of ownership, participation and learning of people involved in the projects. Its design is structured in four groups of elements that aim to answer key questions involved in the creation of a project, namely: how (need, problem solving, partnerships and measurement of results), what (value proposition), by whom (co-responsible, participation, channels and ownership) and how much (spending and funding).